Kepemimpinan Ideal Umar bin Abdul Aziz - M. Anzaikhan khan; Fitri Idani (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2022)
Historically, Islam gave birth to many extraordinary leaders, one of which was Umar bin Abdul Aziz. The modern thinker who intensely discusses the leadership concept of Umar bin Abdul Azis is Khairuddin Faiz. According to Khairuddin Faiz, Umar bin Abdil Azis is an ideal leader who offers various leadership concepts in an implementable manner. This can be seen in the character and policies of Umar bin Abdul Azis when he became the leader of the Muslims (caliphate) in his time. Even though he only served for a short time, the government of Umar bin Abdul Azis had a very significant impact, and brought prosperity to the community. This article belongs to literature research with a qualitative approach. The methodology used is a descriptive analysis study of Khairuddin Faiz's thoughts. The results of the study conclude that being an ideal leader as practiced by Umar bin Abdul Azis consists of various aspects, including; Leaders must be appointed not self-appointed, leaders come to scholars as advisors, leaders must be egalitarian, leaders must be wira'i, and leaders dedicate wealth to the people instead of hoarding wealth.